Beneficial effects of whey protein peptides on muscle loss in aging mice models - Wu, Xin; Yu, Xiaochen; Zhu, Na; Xu, Meihong; Li, Yong (Frontiers in Nutrition, 2022)
Aging-related muscle loss is a hallmark of aging and is the cause of some negative outcomes. An optimized diet and supplements have a positive effect in slowing down the process of muscle loss. D-galactose (d-gal) has been used widely to develop aging model. This study explored the beneficial effects of whey protein peptides (WPPs) on sarcopenia in d-gal-induced aging mice. A total of 72 SPF male C57BL/6N mice were used in this study. Sixty mice were modeled by injected intraperitoneally with d-gal (100 mg/kg body weight for 6 weeks), and the other twelve mice were used as control, and injected with the same amount of normal saline. After 6 weeks, the modeled mice were randomly divided into the model control group, the whey protein group (1.5 g/kg*bw), and three WPPs intervention groups (0.3 g/kg*bw, 1.5 g/kg*bw, 3.0 g/kg*bw), according to serum MDA level. The test samples were orally given to mice by daily garaged. During the 30 days intervention period, the model control group, the whey protein group, and the whey protein peptide group continued receiving intraperitoneal injections of D-galactose, while the control group continued receiving intraperitoneal injections of normal saline. The results showed that WPPs could significantly improve grip strength of aged mice. WPPs could significantly increase lean mass of aged mice, increase muscle weight of gastrocnemius and extensor digitorum longus. WPPs could significantly increase the level of IGF-1 and reduce level of IL-1, IL-6, TNF-α in serum. WPPs could affect the muscle fiber size in d-gal-induced aging mice. Its specific mechanism may be related to the activation of IGF-1/Akt/mTOR protein synthesis signaling pathway and reduction of the level of inflammation. These results indicate that WPPs can improve aging-related sarcopenia. Compared with whey protein, WPPs supplement seems a better form for sarcopenia.